2019
DOI: 10.1002/eco.2075
|View full text |Cite
|
Sign up to set email alerts
|

Does biocrust successional stage determine the degradation of vascular vegetation via alterations in its hydrological roles in semi‐arid ecosystem?

Abstract: Biocrusts may influence soil moisture by changing soil hydrological properties and thus affect the growth of vascular vegetation. However, their effects on soil moisture and vascular vegetation have not been sufficiently evaluated. In this study, five treatments, including bare land with sporadic cyanobacterial biocrusts (BL), lichendominated biocrusts, Artemisia ordosica (AO), A. ordosica with moss biocrusts, and old-aged A. ordosica with moss biocrusts (OAMB), were established to evaluate the effects of bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…This result could be attributed to the higher fine content and polysaccharide content of the moss-covered soils when compared to lichen-covered soils (Table 1). Furthermore, similar to our simulation study, the results of field experiments by Guan and Liu (2019) also found that well-developed mosscovered biocrusts had higher θs than lichen-covered biocrusts, suggesting a higher retention capacity for the moss-covered biocrusts.…”
Section: Determination Of Van Genuchten Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…This result could be attributed to the higher fine content and polysaccharide content of the moss-covered soils when compared to lichen-covered soils (Table 1). Furthermore, similar to our simulation study, the results of field experiments by Guan and Liu (2019) also found that well-developed mosscovered biocrusts had higher θs than lichen-covered biocrusts, suggesting a higher retention capacity for the moss-covered biocrusts.…”
Section: Determination Of Van Genuchten Parameterssupporting
confidence: 88%
“…In comparison to the bare land, greater water-holding capacity on the biocrust-covered soils could lead to an improved water conditions on the soil surface (Fig. 3B; Guan and Liu, 2019). Furthermore, the anchoring structures on lichen-covered soils allows for a longer residence time of the water, which could improve water retention at the soil surface.…”
Section: Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…fine and clay) and polysaccharide content on moss-covered soils when compared to lichen-covered soils (Table 1). Moreover, coinciding with this simulation study, the results of field experiments of Guan and Liu (2019) also reported that well-developed moss biocrusts had higher θ s than lichen biocrusts, suggesting a higher retention capacity for the moss biocrusts.…”
Section: Determination Of Van Genuchten Parameterssupporting
confidence: 87%
“…In addition, the presence of biocrusts and its disturbance alter soil physical properties and subsequently influence soil hydrological processes and thus change plant growth (Guan & Liu, 2019;Havrilla et al, 2019;Xiao & Hu, 2017). Improved knowledge of the hydraulic properties of biocrusts and estimation of soil hydraulic parameters are crucial to improve simulation of infiltration and soil water dynamics in vegetation-soil-water models and have important implications for the simulation of eco-hydrological processes in dryland ecosystems.…”
mentioning
confidence: 99%